PERILAKU MASYARAKAT TERHADAP PENGELOLAAN SAMPAH DI DESA ALLAKUANG KECAMATAN MARITENGNGAE KABUPATEN SIDENRENG RAPPANG - Iin Andini; Lukman Lukman; Ahmad Mannu (JIA: Jurnal Ilmiah Administrasi, 2022)
The purpose of this study is to determine the Behavior of the Villagers Allakuang On Waste Management in the Village Allakuang Kecamatan Maritengngae Kabupaten Sidenreng Rappang.The population in this research is the community with the sex of the men and women who numbered as many as 892 HOUSEHOLDS out of 4 Hamlet, data collection techniques, namely the formula yount with the results of the 128 people, are taken based on probability sampling. The type of research used is descriptive research type is quantitative. Data collection techniques used are observation, questionnaires, literature study and interviews. Data analysis techniques, namely descriptive statistics, quality test data, test, classic assumption test, regression models and hypothesis testing with the help of an SPSS 16.0 and the likert scale. The results showed that the Behavior of the People in the Village Allakuang entered the category of Good with the results of the percentage of the processed questionnaires as many as 79%. Furthermore, the Management of Waste in the Village Allakuang entered the category of Good based on the processed results of the questionnaire with the percentage of 73,12%.